UHPLC‐ESI‐QTOF‐MS2 analysis of Acacia pennata extract and its effects on glycemic indices, lipid profile, pancreatic and hepatorenal alterations in nicotinamide/streptozotocin‐induced diabetic rats - Hui Shao (Food Science & Nutrition, 2022)
Abstract Diabetes mellitus (DM) is a chronic disorder associated with severe metabolic derangement and comorbidities. The constant increase in the global population of diabetic patients coupled with some prevailing side effects associated with synthetic antidiabetic drugs has necessitated the urgent need for the search for alternative antidiabetic regimens. This study investigated the antidiabetic, antioxidant, and pancreatic protective effects of the Acacia pennata extract (APE) against nicotinamide/streptozotocin induced DM in rats. The antidiabetic activity of APE was evaluated and investigated at doses of 100 and 400 mg/kg body weight, while metformin (150 mg/kg bw) was used as a standard drug. APE markedly decreased blood glucose level, homeostatic model assessment for insulin resistance, serum total cholesterol, triglycerides, low‐density lipoprotein, blood urea nitrogen, creatinine, alanine transaminase, aspartate transaminase, and alanine phosphatase levels. Additionally, treatment with APE increased the body weight, serum insulin concentration, and high‐density lipoprotein. Moreover, activities of pancreatic superoxide dismutase, catalase, and glutathione peroxidase were increased, while the altered pancreatic architecture in the histopathological examination was notably restored in the treated rats. Ultra‐high performance liquid chromatography combined with electrospray ionization quadrupole time‐of‐flight mass spectrometry (UHPLC‐ESI‐QTOF‐MS) analysis of APE showcases the prevailing presence of polyphenolic compounds. Conclusively, this study showed the beneficial effects of the Acacia pennata in controlling metabolic derangement, pancreatic and hepatorenal dysfunction in diabetic rats.